Ways to make sunshine ebook - Watson, Renée (Ryan Hart., 2020)
From Newbery Honor and Coretta Scott King Author Award winner Renée Watson, the first book in a young middle grade series about Ryan Hart, a girl who is pure spirit, kindness, and sunshine. Ryan Hart can be and do anything. Her name means "king", that she is a leader, and she is determined to keep growing into the name her parents gave her. She is all about trying to see the best in people, to be a good daughter, sister, and friend. But Ryan has a lot on her mind. For instance: Dad finally has a new job, but money is still tight. That means some changes, like moving into a new (old) house, and Dad working the night shift. And with the fourth-grade talent show coming up, Ryan wonders what talent she can perform on stage in front of everyone without freezing. As even more changes and challenges come her way, Ryan always finds a way forward and shows she is a girl who knows how to glow. Acclaimed author Renée Watson writes her own version of Ramona Quimby, one starring a Black girl and her family, in this start to a charming new series. Acclaim for Ways to Make Sunshine : A New York Times Best Children's Book of the Year | A Parents Magazine Best Book of the Year | A School Library Journal Best Book of the Year | A Kirkus Reviews Best Book of the Year | A Publishers Weekly Best Book of the Year | A WORLD Magazine Best Book of the Year | An Amazon Best Book of the Year